Study Of Soil Chemical Properties In The Use of palawija Cultivation and Community Forests in toho Village Downstream Toho Sub District Mempawah District - Despianto Hutapea; Rita Hayati; Abdul Mujib Alhaddad (Jurnal Sains Pertanian Equator, 2019)
This research is carried on in the Village of Toho Hilir Sub-District Toho Regency Mempawah in three difrent land us, the is Crop, Bare Land and the Community Forest The purpose of this research is to know the Nutrient status of elements N,P,K, C-Organic, AL-Exchangable, CEC and Base Saturation. The point observation of this research using a system of diagonal and random with 5 spot observations of the Crops Cultivated and Forest, with depth 0-30 cm. Result of soil analysis showed that pH of the soil in the Crop Cultivated Land, Bare Land, Community Forest is high C-Organic in Land categorized as low, Bare Land is medium Crop and Community Forest is medium, N-Total in Crop Land is categorized as medium, Bare Land is medium and Community Forest also medium criteria, available phosfor on Crop Land very high, Bare Land high and Community Forest are high criteria, potassium Exchange in Crop Land is categorized as low, Bare Land including low criteria and Community Forest including low criteria, AL-Exchangable in Crop Plant Land very low in criteria, Bare Land very low and Community Forest low, CEC in Crop Land is categorized as low, Bare Land low and Community Forest low and base saturation in Crop Land is categorized as low, Bare Land very low and Community Forest very low.Keywords : Community Forest, Bare Land, Palawija, Soil Chemical Properties